Bioethanol Production from Iles-Iles (Amorphopallus campanulatus) Flour by Fermentation using Zymomonas mobilis - Kusmiyati Kusmiyati; H Hadiyanto; Indah Kusumadewi (International Journal of Renewable Energy Development, 2016)
Due to the depletion of fossil oil sources, Indonesia attempts to search new source of bioenergy including bioethanol. One of this sources is Iles-iles tubers (Amorphophallus campanulatus), which is abundantly available in Java Indonesia. The carbohydrate content in Iles-Iles tuber flour was 77% and it can be converted to ethanol by three consecutive steps methods consist of liquefaction-saccharification using α and β-amylase, respectively and then followed by fermentation by using Z. mobilis. The objective of this research was to convert the Iles-iles flour to bioethanol by fermentation process with Z.mobilis. The ethanol production process was studied at various starch concentration 15-30% g/L, Z. mobilis concentration (10-40%) and pH fermentation of (4-6). The result showed that the yield of bioethanol (10.33%) was the highest at 25% starch concentration and 25% of Z.mobilis concentration. The optimum conditions was found at 4.5, 30°C, 10%, 120 h for pH, temperature, Z. mobilis concentration and fermentation time, respectively  at which  ACT tuber flour produced a maximum ethanol of 10.33 % v/v.Article History: Received November 12nd 2015; Received in revised form January 25th 2016; Accepted January 29th 2016; Available onlineHow to Cite This Article: Kusmiyati , Hadiyanto,H  and Kusumadewi, I (2016). Bioethanol Production from Iles-Iles (Amorphopallus campanulatus) Flour by Fermentation using Zymomonas mobilis. Int. Journal of Renewable Energy Development, 9(1), 9-14http://dx.doi.org/10.14710/ijred.5.1.9-14